(untitled) (Italian Review of Legal History, 2015)
Between 1883 and 1893, seven Bills aimed at the establishment of the board of probiviri for industry followed one another in the Parliament. In the intention of the Italian legislator, this law was to become part of the wider framework of the “social legislation,” as a means of pacification of conflicts between workers and employers. An examination of the parliamentary works makes resistance and doubts about the to-be-constituted boards come to light, mainly catalysed around the need to avoid the creation of a special judiciary, which went to create a vulnus in the principle of unity in the jurisdiction, so strongly desired and defended by the unitary legislator. The office and commission files, reports and discussions in the chamber return a vivid and polyhedral framework of the various positions taken up during the years. Opposing the side of those who bluntly against the institute, for fear that a special judge would be appointed, were the positions of those who wanted to see a mere conciliatory jurisdiction, as well as those who, of a more radical opinion, solicited a judiciary with technical competence and equity which went to fill the gap represented by the absence of a legislation regulating labour. The final draft of the law would produce a hybrid authority, with mixed judging and conciliating functions, rising questions, from its early applications, about the nature of the authority, the powers granted thereto, the rite to be followed; questions, of which a careful and shrewd doctrine would become an interpreter.